Echoes of Universalist Testament Literature in Christian and Rabbinic Texts. (6th January 2016) - Simkovich, Malka Z.
Abstract : The ancient text known as the Testament of Abraham is preserved in Coptic in the same codex as two other works, the Testament of Isaac and the Testament of Jacob. These testaments were probably written in the late first or early second centuries CE by Jewish writers, although the manuscript of the Coptic codex containing them is dated to 962. These books were considered part of the "testament" literary genre, which featured a biblical hero imparting his last words of religious wisdom to his family gathered at his bedside. Scholars agree that the stylistic and theological differences among these three testaments indicate that they were not written by the same author. Yet a close reading reveals that the Testament of Isaac is dependent on the Testament of Abraham, and that the Testament of Jacob is dependent on the two earlier texts. Moreover, the Testament of Abraham and the Testament of Isaac share similarities that distinguish them from the Testament of Jacob: unlike the Testament of Jacob, the Testament of Abraham and the Testament of Isaac reflect a universalist worldview that depicts a God concerned for all humankind, not only for his chosen people. This God reigns over all people, and themes specific to the Christian and Jewish faiths are virtually absent. Later Christian and Jewish literature concerning the theme of divine judgment exhibits elements that may reflect an awareness of a written or oral tradition that appears in the Testament of Abraham and the Testament of Isaac. The images of judgment and punishment, especially those in the Testament of Abraham, appear in the second-century Apocalypse of Peter and the fourth-century Vision of Paul, which is also known as the Apocalypse of Paul. Likewise, midrashic traditions regarding Abraham and Moses are reminiscent of traditions found in these testaments, particularly the Testament of Abraham. The possibility that early Christian apocalyptic texts were aware of these testaments is grounded in the fact that scholars give these texts a common place of origin, Egypt. The provenance of the midrashic texts is more difficult to identify, but because they share literary elements and theological concerns with the Testament of Abraham and the Testament of Isaac, I suggest that the authors of these midrashic traditions had access to written or oral traditions prominent in these testaments. This paper will examine early Christian apocalyptic and early Jewish midrashic texts that modify some of the traditions prominent in these testaments in order to accommodate their nonuniversalist rabbinic or early Christian worldviews.